Interfaces in functional discourse grammar Theory and Applications - Contreras-García, Lucia; Esteban, Avelino Corral; García Velasco, Daniel; Giomi, Riccardo; Hengeveld, Kees; Keizer, Evelien; Klumm, Matthias; Leufkens, Sterre; Mackenzie, Lachlan; Olthof, Marieke; Portero Muñoz, Carmen; Schwaiger, Thomas; et al. (Trends in Linguistics. Studies and Monographs [TiLSM] ;, 2021)
In grammar design, a basic distinction is made between derivational and modular architectures. This raises the question of which organization of grammar can deal with linguistic phenomena more appropriately. The studies contained in the present volume explore the interface relations between different levels of linguistic representation in Functional Discourse Grammar as presented in Hengeveld and Mackenzie (2008) and Keizer (2015). This theory analyses linguistic expressions at four linguistic levels: interpersonal, representational, morphosyntactic and phonological. The articles address issues such as the possible correspondences and mismatches between those levels as well as the conditions which constrain the combinations of levels in well-formed expressions. Additionally, the theory is tested by examining various grammatical phenomena with a focus both on the English language and on typological adequacy: anaphora, raising, phonological reduction, noun incorporation, reflexives and reciprocals, serial verbs, the passive voice, time measurement constructions, coordination, nominal modification, and connectives. Overall, the volume provides both theoretical and descriptive insights which are of relevance to linguistics in general.